Hadron-hadron interactions in Coulomb gauge QCD - Szpigel, Sérgio; Krein, Gastão Inácio [UNESP]; Marques de Carvalho, R. S. [UNESP] (Sociedade Brasileira de Física, 2004)
We describe the derivation of an effective Hamiltonian which involves explicit hadron degrees of freedom and consistently combines chiral symmetry and color confinement. We use a method known as Fock-Tani (FT) representation and a quark model formulated in the context of Coulomb gauge QCD. Using this Hamiltonian, we evaluate the dissociation cross section of J/psi in collision with rho.